ANALISIS NERACA AIR PADA SUB DAERAH ALIRAN SUNGAI CODE YOGYAKARTA - Alvin Pradana; Ratna Septi Hendrasari (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract Water is one of the sources of human life. Population growth continues to increase and results in higher utilization of water sources. This will certainly affect the availability of water in the city of Yogyakarta. Water balance is a comparison between the water availability potential and the water demand of a place in a certain period. Water balance analysis is useful for knowing the amount of excess water (surplus) or lack of water (deficit) so that water use can be managed as well as possible. The calculation was done by analyzing the 10-year rainfall data using the Thiessen Polygon method to obtain the mean rainfall value. The available debit was calculated using the F.J. Mock method. The dependable discharge was calculated with 80% reliability from the 10-year debit data. The debit data was sorted from the largest to the smallest value, so that a probability value of 80% was obtained from the interpolation of the data sequence. Water demand was calculated based on the irrigation planning standard (KP-01). The results of the study show that the average water availability in the sub-watershed of Code River Yogyakarta was 527.92lt/sec. Based on the results of the analysis, the highest water deficit occurred in the first October at 278.40 l/sec and the lowest deficit was in the second July at 73.01 l/sec. However, the availability of water in certain months was quite abundant. Therefore, it is necessary to do a special study so that water is not wasted and can be used to cover water shortages in dry months. Keywords: Water balance, Water availability, Water demand, Code river, Thiessen polygon, FJ mock